2004
DOI: 10.1590/s0103-84782004000200040
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros biométricos de fruto, endocarpo e semente de butiazeiro

Abstract: O butiazeiro (Butia capitata (Mart.) Becc.) ocorre naturalmente no sul do Brasil. Esta espécie possui potenciais ecológicos, ornamentais e industriais escassamente explorados. Informações sobre variações biométricas de tamanho e peso de frutos e sementes, bem como sua correlação, podem fornecer subsídios para seleção de sementes com maior potencial de germinação e vigor. Os objetivos deste trabalho foram determinar as variações de tamanho e peso de frutos, endocarpos e sementes botânicas de butiazeiro e suas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 3 publications
2
10
0
17
Order By: Relevance
“…Pedron et al (2004) likewise observed positive correlations between fruit volume and endocarp volume and seed numbers in Butia capitata (Arecaceae). Considering the lack of information in the literature on criteria for characterization palm fruits, the criteria proposed in this paper can be used in studies on the taxonomy and breeding in this family.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Pedron et al (2004) likewise observed positive correlations between fruit volume and endocarp volume and seed numbers in Butia capitata (Arecaceae). Considering the lack of information in the literature on criteria for characterization palm fruits, the criteria proposed in this paper can be used in studies on the taxonomy and breeding in this family.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, these analyses provide important information for selecting diaspores for propagation (PEDRON et al, 2004) and for conservation efforts -thus favoring the rational use of valuable natural resources (SOLER et al, 2007). The characterization of babassu fruits derived from populations in northern Minas Gerais State will contribute to our knowledge of the complex taxonomy of this group (in light of the recent transfer of species of the genus Orbignya to Attalea) (LORENZI et al, 2004(LORENZI et al, , 2010, the great morphological diversity among the fruits of the different species TEIXEIRA, 2008), and the occurrence of natural hybridization (BALICK et al, 1987;LORENZI et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A massa fresca média do fruto (Tabela 1) se apresentou bastante semelhante aos resultados de Rivas & Barilani (2004), porém diferentes dos relatados por Pedron et al (2004), onde a média da massa é igual a maior massa média do fruto detectado nesse estudo. Essa discordância pode estar associada a vários aspectos, dentre eles, tamanho da amostra, condições edafo-ambientais e origem genética do material estudado.…”
Section: Para B Odorataunclassified
“…Esses resultados são parecidos com os descritos por Pedron et al (2004), Rivas & Barilani (2004) e Nascimento et al (2007). Nesse estudo a polpa representa em média aproximadamente 80% do fruto (Tabela 1), porém já Rivas & Barilani (2004) verificaram que a polpa consiste em 70% do fruto.…”
Section: Para B Odorataunclassified
See 1 more Smart Citation